2017
DOI: 10.1097/bpo.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

Growth Modulation in Achondroplasia

Abstract: Growth modulation is an effective means for deformity correction in the setting of achondroplasia. However implantation may need to be done earlier than would be typical for patients without achondroplasia. Osteotomy may still be required after growth modulation for incomplete correction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 14 publications
0
21
0
1
Order By: Relevance
“…Nonetheless, impressive outcomes have been demonstrated (P. Stevens, personal communication 2015). Limited published data regarding its use in those with achondroplasia [294] suggest that at least partial correction of malalignment can be accomplished. There even is anecdotal evidence that correction in one plane (varus deformity) will secondarily results in improvement of the other components (internal torsion and lateral instability) (P. Stevens, personal communication 2015).…”
Section: Natural History and Managementmentioning
confidence: 99%
“…Nonetheless, impressive outcomes have been demonstrated (P. Stevens, personal communication 2015). Limited published data regarding its use in those with achondroplasia [294] suggest that at least partial correction of malalignment can be accomplished. There even is anecdotal evidence that correction in one plane (varus deformity) will secondarily results in improvement of the other components (internal torsion and lateral instability) (P. Stevens, personal communication 2015).…”
Section: Natural History and Managementmentioning
confidence: 99%
“…Several reports of smaller series of patients with different conditions have been published. McClure et al 53 reported four patients with achondroplasia and genu varus with bilateral distal femoral and proximal tibial growth modulation in three of them and only tibial correction in the remaining. All limbs had some improvement of alignment; however, one patient went on to bilateral osteotomies.…”
Section: Correction Of Angular Deformitiesmentioning
confidence: 99%
“…The consideration, however, of remaining growth from the instrumented physis is an important consideration in the setting of short stature conditions. McClure et al 20 reported on growth modulation about the knee to correct genu varum in 4 patients with achondroplasia and noted only 1 limb corrected to a neutral axis alone with the implantation performed at 5 years of age. In a larger series of skeletal dysplasia patients undergoing hemiepiphysiodesis, Yilmaz et al 21 found absence of sufficient remaining growth to be a reason for lack of benefit in a subset of their patients as well.…”
Section: Discussionmentioning
confidence: 99%
“…Lower extremity deformity correction by guided growth has also been reported in metabolic bone conditions such as renal osteodystrophy, nutritional rickets, and Morquio-Brailsford syndrome 16–18. Guided growth has also been reported in the setting of various skeletal dysplasias19–21 and as a case report in the setting of OI 22. To date, to our knowledge, there is no report of a series of deformity correction by growth modulation in the setting of OI.…”
mentioning
confidence: 98%